Republic of Slovenia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper provides a quantitative assessment of the determinants of inflation in Slovenia, and evaluates the likelihood of the Maastricht inflation criterion being met. It concludes that on the basis of currently identified policies, Slovene inflation will likely remain above the Maastricht criterion over the assessment period. The IMF staff analysis suggests that the economic slowdown related to the unfavorable external environment contributed about two-thirds to disinflation in 2003. This paper also analyzes the direct fiscal implications of European Union accession on Slovenia.